Multimodal partial volume correction: Application to [11C]PIB PET/MRI myelin imaging in multiple sclerosis. Issue 12 (December 2017) - Grecchi, Elisabetta; Veronese, Mattia; Bodini, Benedetta; García-Lorenzo, Daniel; Battaglini, Marco; Stankoff, Bruno; Turkheimer, Federico E
The [ 11 C]PIB PET tracer, originally developed for amyloid imaging, has been recently repurposed to quantify demyelination and remyelination in multiple sclerosis (MS). Myelin PET imaging, however, is limited by its low resolution that deteriorates the quantification accuracy of white matter (WM) lesions. Here, we introduce a novel partial volume correction (PVC) method called Multiresolution–Multimodal Resolution-Recovery (MM-RR), which uses the wavelet transform and a synergistic statistical model to exploit MRI structural images to improve the resolution of [ 11 C]PIB PET myelin imaging. MM-RR performance was tested on a phantom acquisition and in a dataset comprising [ 11 C]PIB PET and MR T1- and T2-weighted images of 8 healthy controls and 20 MS patients. For the control group, the MM-RR PET images showed an average increase of 5.7% in WM uptake while the grey-matter (GM) uptake remained constant, resulting in +31% WM/GM contrast. Furthermore, MM-RR PET binding maps correlated significantly with the mRNA expressions of the most represented proteins in the myelin sheath (R 2  = 0.57 ± 0.09). In the patient group, MM-RR PET images showed sharper lesion contours and significant improvement in normal-appearing tissue/WM-lesion contrast compared to standard PET (contrast improvement > +40%). These results were consistent with MM-RR performances in phantom experiments.